Deducing formation routes of oxylipins by quantitative multiple heart-cutting achiral-chiral 2D-LC-MS - Nadja Kampschulte; Rebecca Kirchhoff; Ariane Löwen; Nils Helge Schebb (Journal of Lipid Research)
Several oxylipins are regulators of inflammation. They are formed by enzymes such as lipoxygenases or cyclooxygenases, but also stereorandomly by autoxidation. Reversed-phase liquid chromatography-tandem-mass-spectrometry (LC-MS/MS) methods for oxylipin quantification do not separate enantiomers. Here, we combine sensitive and selective oxylipin analysis with chiral separation using two-dimensional (2D)-LC-MS/MS. By multiple heart-cutting, the oxylipin peaks are transferred onto a chiral column. 45 enantiomeric pairs of (di-)hydroxy-fatty acids are separated with full gradient elution within 1.80 min, yielding lower limits of quantification <1 pg on the column. Concentrations, as well as enantiomeric fractions of oxylipins, can be determined, even at low concentrations or at high enantiomeric excess of one isomer. The developed achiral-chiral multiple heart-cutting 2D-LC-MS/MS method offers unprecedented selectivity, enabling a better understanding of the formation routes of these lipid mediators. This is demonstrated by distinguishing the formation of hydroxy-fatty acids by (acetylated) cyclooxygenase-2 and radical-mediated autoxidation. Applying the method to human M2-like macrophages, we show that the so-called specialized pro-resolving mediators (SPM) 5,15-DiHEPE and 7,17-DiHDHA as well as 5,15-DiHETE were present as (S,S)-enantiomers, supporting their enzymatic formation. In contrast, at least eight isomers (including protectin DX but not neutroprotectin D1) of 10,17-DiHDHA are present in immune cells, indicating formation by autoxidation. In the human plasma of healthy individuals, none of these dihydroxy-fatty acids are present. However, we demonstrate that all four isomers quickly form via autoxidation if the samples are stored improperly. Dihydroxy-FA should only be reported as SPM, such as resolvin D5 or resolvin E4, if an enantioselective analysis as described here has been carried out.